ANALYSIS OF FACTORS AFFECTING THE TIMELINESS OF FINANCIAL REPORTING ON BIMBEL AHE IN PATI - Arini Novandalina; Fidyah Yuli Ernawati; Rokhmad Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the factors that affect the timeliness of financial reporting at Bimbel Ahe in Pati. Financial ratios are one way to assess the timeliness of financial reporting in companies. The population in this study is the financial statements of Bimbel Ahe Pati for the period 2016-2020. The sample in this study is the financial statements of AHE Bimbel in Pati. The independent variable of this research is profitability is measured by return on assets (ROA), Leverage is measured by debt assets ratio (DAR) and internal audit records. While the dependent variable is the timeliness of financial reporting. Data collection techniques using documentation and analysis techniques with logistic regression. The results showed that the profitability variable in this study was return on assets (ROA) showing the regression coefficient value of 109.722 with a sig value. of 0.626 above the significance of 0.05 (5%), thus it is proven that profitability has no effect on the timeliness of the presentation of financial statements, the leverage variable in this study is the debt to asset ratio (DAR) showing the regression coefficient value of -1.015 with a sig value . of 0.912 above the significance of 0.05 (5%), thus it is proven that leverage has no effect on the timeliness of the presentation of financial statements and the internal audit record variable in this study is the opinion of a public accountant or auditor about the financial statements whether qualified or qualified opinion (WDP) and unqualified opinion or unqualified (WTP) show the regression coefficient value of 18.869 with a value of sig. of 0.998 above the significance of 0.05 (5%), thus it is evident that the internal audit records have no effect on the timeliness of the presentation of financial statements. Bimbel Ahe is expected that profitability ratios, leverage and internal audit records can be useful and used as consideration by companies in completing and submitting financial reports on time because timely completion of financial statements can give a positive impression and can show the company's performance is good or not. not and what has been done by the company's management can be seen from the financial statements and can be used to take future policies. And because in this study only use return on assets (ROA) to measure profitability. For this reason, further research is expected to use other proxies such as return on equity (ROE), profit margin to measure profitability. Thus, it is possible that the results will significantly affect the accuracy of the presentation of financial statements